UPDATE ON THE LABORATORY DIAGNOSIS OF INVASIVE FUNGAL INFECTIONS - Elena De Carolis; Riccardo Torelli; Brunella Posteraro; Patrizia Posteraro; Maurizio Sanguinetti (Mediterranean Journal of Hematology and Infectious Diseases)
Recent advances in the management of patients with haematological malignancies and transplant recipients have paralleled an increase in the incidence of fungal diseases due to pathogenic genera such as Candida and Aspergillus and the emergence of less common genera including Fusarium and Zygomycetes. Despite availability of new antifungal agents these opportunistic infections have high mortality. Rapid and reliable species identification is essential for antifungal treatment, but detection of the increasing diversity of fungal pathogens by conventional phenotypic methods remains difficult and time-consuming, and the results may sometimes be inconclusive, especially for unusual species. New diagnostic techniques (e.g., 1,3-beta-d-glucan detection) could improve this scenario, although further studies are necessary to confirm their usefulness in clinical practice.